2023
DOI: 10.1155/2023/9950331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dry–Wet Cycling on the Degradation Characteristics and Mechanisms of Red Sandstone

Abstract: The physical and mechanical parameters and degradation mechanisms of red sandstone in the Mount Wuyi scenic area were studied under the action of dry–wet cycles. Dry–wet cycle, acoustic wave velocity, water saturation rate, and triaxial compression tests were conducted, aided by scanning electron microscopy and X-ray diffraction testing techniques. The study’s results show that the dry–wet cycle effect on red sandstone is a major factor in the degradation of its physical and mechanical parameters and that its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Using the water-absorbing properties of sponge sheets to simulate the external erosive environment, wet and dry cycle tests were carried out on two types of red sandstone. Following the test method described in references [23,29], all specimens processed were dried in a drying oven at a temperature of 80 • C for 24 h and cooled for 1 h. The sponge sheet saturated with sulfate solution was placed on top of the machined specimens to erode the specimens for 24 h, which is one dry and one wet cycle. The experiment found that after one cycle, the ultrasonic data change is small, so take every two cycles to measure and record the ultrasonic velocity of the specimen and twenty wet and dry cycles to obtain ten sets of data.…”
Section: Experimental Programme and Test Methodsmentioning
confidence: 99%
“…Using the water-absorbing properties of sponge sheets to simulate the external erosive environment, wet and dry cycle tests were carried out on two types of red sandstone. Following the test method described in references [23,29], all specimens processed were dried in a drying oven at a temperature of 80 • C for 24 h and cooled for 1 h. The sponge sheet saturated with sulfate solution was placed on top of the machined specimens to erode the specimens for 24 h, which is one dry and one wet cycle. The experiment found that after one cycle, the ultrasonic data change is small, so take every two cycles to measure and record the ultrasonic velocity of the specimen and twenty wet and dry cycles to obtain ten sets of data.…”
Section: Experimental Programme and Test Methodsmentioning
confidence: 99%